Vitamin D status is inversely associated with anemia and serum erythropoietin during pregnancy(1)(2) - Thomas, Carrie E (Am J Clin Nutr, 2015)
Background: Vitamin D and iron deficiencies frequently co-exist. It is now appreciated that mechanistic interactions between iron and vitamin D metabolism may underlie these associations. Objective: We examined interrelations between iron and vitamin D status and their regulatory hormones in pregnant adolescents, who are a group at risk of both suboptimal vitamin D and suboptimal iron status. Design: The trial was a prospective longitudinal study of 158 pregnant adolescents (aged ≤18 y). Maternal circulating biomarkers of vitamin D and iron were determined at midgestation (∼25 wk) and delivery (∼40 wk). Linear regression was used to assess associations between vitamin D and iron status indicators. Bivariate and multivariate logistic regressions were used to generate the OR of anemia as a function of vitamin D status. A mediation analysis was performed to examine direct and indirect relations between vitamin D status, hemoglobin, and erythropoietin in maternal serum. Results: Maternal 25-hydroxyvitamin D [25(OH)D] was positively associated with maternal hemoglobin at both midgestation and at delivery (P < 0.01 for both). After adjustment for age at enrollment and race, the odds of anemia at delivery was 8 times greater in adolescents with delivery 25(OH)D concentrations <50 nmol/L than in those with 25(OH)D concentrations ≥50 nmol/L (P <0.001). Maternal 25(OH)D was inversely associated with erythropoietin at both midgestation (P <0.05) and delivery (P <0.001). The significant relation observed between 25(OH)D and hemoglobin could be explained by a direct relation between 25(OH)D and hemoglobin and an indirect relation that was mediated by erythropoietin. Conclusions: In this group of pregnant adolescents, suboptimal vitamin D status was associated with increased risk of iron insufficiency and vice versa. These findings emphasize the need for screening for multiple nutrient deficiencies during pregnancy and greater attention to overlapping metabolic pathways when selecting prenatal supplementation regimens.